Digital Money Across Borders : Macro-Financial Implications. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
Rapid ongoing progress with digital technologies has increased the prospects for adoption of new forms of digital money for both domestic and international transactions. These include central bank digital currencies (CBDCs) and the so-called global stable coins (GSCs) proposed by large technological companies or platforms. This paper explores the complex interactions between the incentives to adopt and use CBDCs and GSCs across borders and discusses the potential macro-financial effects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet